MODEL PENGEMBANGAN KURIKULUM DAN STRATEGI PEMBELAJARAN PENDIDIKAN TINGGI AKUNTANSI BERBASIS SOSIOLOGI KRITIS, KREATIVITAS, DAN MENTALITAS - HAMZAH, ARDI (Jurnal Ilmiah Akuntansi dan Bisnis, 2009)
Curriculum of accounting in higher education level in Indonesia has been stagnant, static, and materiality oriented. It is said to be static because the curriculum does not contain creativity aspect. Furthermore, mentality values, such as honesty and fairness are still hardly found in the curriculum. The development of critical sociology, creativity, and mentality-based curriculum must be supported by strategy that not only consists of theoretical explanation, but also innovative learning strategies. An innovative learnings strategy helps creativity involving student directly in the whole learnigs process.
Keywords: curriculum, critical sociology, creativity, mentality, strategy